2012
DOI: 10.1007/s11605-012-1965-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Percutaneous Cholecystostomy for Acute Cholecystitis: a Single-Center Experience

Abstract: In-patients or those with septic shock or renal insufficiency have worse outcome. Prolonged drainage duration and high CRP level predict early recurrence. Removal of the drainage tube is recommended after resolution of the acute illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 26 publications
3
67
3
1
Order By: Relevance
“…25 The rate of complications following LC in the elderly is estimated to be 22%. 5,7,9,[26][27][28] In the present study, a similar rate of major morbidity was observed (23%) to the rates reported for other series of patients undergoing interval cholecystectomy after PCY (Table 4). [2][3][4][5][6][7][8][9]29 Routine drainage at cholecystectomy did not prevent abscess formation in five patients.…”
Section: Surgical Techniquesupporting
confidence: 90%
See 1 more Smart Citation
“…25 The rate of complications following LC in the elderly is estimated to be 22%. 5,7,9,[26][27][28] In the present study, a similar rate of major morbidity was observed (23%) to the rates reported for other series of patients undergoing interval cholecystectomy after PCY (Table 4). [2][3][4][5][6][7][8][9]29 Routine drainage at cholecystectomy did not prevent abscess formation in five patients.…”
Section: Surgical Techniquesupporting
confidence: 90%
“…Mortality rates have been reported from 0% to 15% and morbidity rates from 0% to 25%. [2][3][4][5][6][7][8][9] Furthermore, as the majority of patients do not have definitive surgery, recurrent AC is common. 10 This study was performed to quantify the risk of short and long-term morbidity and mortality for this cohort, using recognised scoring systems for co-morbidities and complications.…”
mentioning
confidence: 99%
“…[2] PC became a recognized temporizing measure for patients with cholecystitis, either with or without cholelithiasis, who were too debilitated or acutely ill to undergo an emergent surgical cholecystectomy, for which rates of morbidity up to 41% and perioperative mortality up to 18% have been reported. [3] Recently, PC has also been proposed as a preferred therapeutic intervention, sometimes definitively, in pregnant patients [4] and in chronic hemodialysis patients. [5] However, a Cochrane Review from 2013 found that more information is still needed to determine the role of PC in high-risk surgical patients.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous cholecystostomy (PC) or percutaneous transhepatic gallbladder drainage (PTGBD) is an alternative treatment for acute cholecystitis in patients who are deemed to be at high surgical risk (1). The perioperative mortality rate of early laparoscopic cholecystectomy is about 1% in low-risk patients (2,3), but in patients who are elderly or who have severe comorbidities, the morbidity rises to 41%, and perioperative mortality increases to 18% (1).…”
Section: Introductionmentioning
confidence: 99%
“…The perioperative mortality rate of early laparoscopic cholecystectomy is about 1% in low-risk patients (2,3), but in patients who are elderly or who have severe comorbidities, the morbidity rises to 41%, and perioperative mortality increases to 18% (1). PTGBD is a safer, minimally invasive procedure for high-risk patients who do not respond to conservative treatment.…”
Section: Introductionmentioning
confidence: 99%